1974
DOI: 10.1029/rs009i011p00895
|View full text |Cite
|
Sign up to set email alerts
|

A summary of vertical incidence radio observations of ionospheric modification

Abstract: Within the past four years, experiments with high power, high frequency radio waves have proved the feasibility of temporarily altering the ionosphere's properties. Many different radio and photometric effects have been observed as a result of the ionospheric modification. This paper provides a survey of some of the effects observed with vertical incidence radio techniques when the US Department of Commerce's Platteville facility, near Boulder, Colorado, is used to illuminate the overhead ionosphere with an eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 12 publications
2
32
0
Order By: Relevance
“…The resulting expected deepening of the duct locally moves the upper hybrid resonance height upward. Since in the L-mode the wave electric field is perpendicular to B 0 at higher plasma densities than in the O-mode, the L-mode facilitates excitation of upper hybrid phenomena localized in the density depletions of small-scale striations (Vas'kov and Gurevich, 1976;Dysthe et al, 1982;Gurevich et al, 1995;Istomin and Leyser, 1997) and associated anomalous absorption deeper into the plasma (at higher ambient plasma densities) and in a wider altitude range than for pure Omode propagation. The duct, so to speak, tells the pump wave where to propagate and the pump wave tells the duct where to deepen, which may lead to self-focusing in magnetic zenith.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting expected deepening of the duct locally moves the upper hybrid resonance height upward. Since in the L-mode the wave electric field is perpendicular to B 0 at higher plasma densities than in the O-mode, the L-mode facilitates excitation of upper hybrid phenomena localized in the density depletions of small-scale striations (Vas'kov and Gurevich, 1976;Dysthe et al, 1982;Gurevich et al, 1995;Istomin and Leyser, 1997) and associated anomalous absorption deeper into the plasma (at higher ambient plasma densities) and in a wider altitude range than for pure Omode propagation. The duct, so to speak, tells the pump wave where to propagate and the pump wave tells the duct where to deepen, which may lead to self-focusing in magnetic zenith.…”
Section: Discussionmentioning
confidence: 99%
“…L-mode propagation, therefore, could account for the strong plasma response observed in magnetic zenith. Already, early experiments in the 1970s showed that HF pumping can facilitate L-mode propagation and associated O-Z conversion, as evidenced by the appearance of socalled Z traces in ionograms (Utlaut and Violette, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…With the beginning of the heating experiments, the occurrence of artificial F -spread was detected in the ionosphere, indicating that inhomogeneities with scales l ⊥ from several hundred meters to several kilometers across the geomagnetic field are formed when the ionospheric plasma is affected by a highpower short radio wave [3,4]. Presumably, large-scale artificial ionospheric inhomogeneities with l ⊥ greater than a few kilometers appear as a result of natural plasma-density inhomogeneities enhanced in the field of a high-power radio wave [5].…”
Section: Introductionmentioning
confidence: 98%
“…In particular, many experimental studies have been applied to the large-scale F-region modification by powerful HF radio waves and many interesting results were obtained (Utlaut and Violette, 1974;Gordon and Carlson, 1974;Mantas et al, 1981;Jones et al, 1986;Djuth et al, 1987;Duncan et al, 1988;Hansen et al, 1992;Mantas, 1994;Honary et al, 1995;Robinson et al, 1996;Frolov et al, 1997;Gustavsson et al, 2001;Rietveld et al, 2003;Ashrafi et al, 2007;Clausen et al, 2008;Pedersen et al, 2008). It turns out that significant variations in the electron temperatures and densities can be produced by powerful HF waves in the F-layer.…”
Section: Introductionmentioning
confidence: 98%